Multi-scale synthetic aperture radar remote sensing for archaeological prospection in Han Hangu Pass, Xin'an China. Issue 1 (2nd January 2017) - Chen, Fulong; Jiang, Aihui; Tang, Panpan; Yang, Ruixia; Zhou, Wei; Wang, Hongchao; Lu, Xin; Balz, Timo
ABSTRACT: Increasing availability of multi-resolution synthetic aperture radar (SAR) data enabled us to demonstrate the benefits of the existing imaging solutions offered by radar satellites for purposes of archaeological prospection. In this study, mid-resolution L-band phased array type L-band synthetic aperture radar (PALSAR) to high-to-very-high-resolution X-band TerraSAR-X/TanDEM-X TerraSAR-X add-on for digital elevation measurements (TanDEM-X) (Stripmap/Staring Spotlight) images were synergistically applied for the archaeological prospection at the Han Hangu Pass, in Xin'an, China. First, the evidence and the stretching direction of the outer walls of the pass were identified from the temporal-averaged products of PALSAR and the terrain from TanDEM Co-registered Single-Look Data. Then, the spatial layout of archaeological monuments (previously documented as well as recently discovered) was observed in the visualization-enhanced Staring Spotlight TerraSAR-X imagery owing to its high spatial and radiometric resolution. The findings of this study highlight the effectiveness of using integrated multi-scale SAR remote sensing data from different platforms in archaeology.